2000
DOI: 10.1037/0021-843x.109.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating gene × psychological risk factor effects in the pathogenesis of anxiety: A new model approach.

Abstract: The present study evaluated the singular and interactive effects of a functional polymorphism (variation) in the serotonin transporter (5-HTT) gene and a psychological trait (anxiety sensitivity [AS], i.e., fear of arousal symptoms) in predicting subjective and physiological responses to a 35% carbon dioxide (CO2) challenge in a community sample (N = 72). Genotypes were divided into 2 groups in accord with prior research. Findings were partially supportive of the hypothesized risk model. These indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 71 publications
4
25
1
Order By: Relevance
“…11,18,24,31 In one study 21 there was insufficient data to test for departure from HW equilibrium. In two studies data were not reported in a format that enabled their inclusion in the subsequent meta-analysis 28,31 and attempts to contact the authors of these studies to request data in an appropriate format were unsuccessful. A total of 24 studies therefore contributed to the meta-analysis, of which three reported genotype frequencies that deviated from HW equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…11,18,24,31 In one study 21 there was insufficient data to test for departure from HW equilibrium. In two studies data were not reported in a format that enabled their inclusion in the subsequent meta-analysis 28,31 and attempts to contact the authors of these studies to request data in an appropriate format were unsuccessful. A total of 24 studies therefore contributed to the meta-analysis, of which three reported genotype frequencies that deviated from HW equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…Pertinently, another study found that healthy females with the LL genotype were more sensitive to CCK-4-induced panic attacks than those who are carriers of S allele (Maron et al, 2004b). Also Schmidt et al (2000) reported that subjects homozygous for the long variant were at greater risk for behavioral hyper-reactivity to 35% CO 2 challenge than those with short-allele genotypes. On the contrary, in patients with PD, CO 2 reactivity was not influenced by 5-HTTLPR genetic variants (Perna et al, 2004).…”
Section: -Htt Genementioning
confidence: 99%
“…It consists of a 44-base pair (bp) insertion/deletion and, in vitro, the basal activity of the long (l) variant was more than twice that of the short (s) one, suggesting that serotonin transporter gene transcription is modulated by such variants Lesch et al, 1996]. Schmidt et al [2000] recently reported a significant difference in subjective reactivity to CO 2 inhalation between 5-HTTLPR genotype groups in healthy subjects. In their sample, subjects homozygous for the long variant (l) appear to be at risk for behavioral hyperreactivity to the 35% CO 2 inhalation test.…”
mentioning
confidence: 97%